Polyphenylene sulfide composition as well as preparation method and application thereof
By preparing a polyphenylene sulfide composition containing PPS resin and flat glass fiber and controlling its physical indicators, the problem that traditional welding technology is difficult to meet the high precision and high strength requirements of PPS materials is solved, and efficient laser welding effect is achieved.
Patent Information
- Application Number
- CN202510017328.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional welding technology is difficult to meet the high precision and high strength requirements of polyphenylene sulfide (PPS) materials in precision manufacturing and complex structural parts, especially because the anisotropic crystal structure of its crystalline polymer materials affects the laser transmittance of the material.
By preparing a polyphenylene sulfide composition, it contains 60 to 85 parts by weight of PPS resin and 15 to 40 parts by weight of flat glass fiber, and controlling the crystallization temperature, melt index and end-chlorine content of the PPS resin to satisfy a specific relationship, so as to reduce the crystallinity of the composition and improve the laser transmittance.
The laser transmittance and laser welding effect of the polyphenylene sulfide composition are improved, making it suitable for laser welding of automobiles, electronics and other related parts.
Smart Images

Figure BDA0005230281160000051 
Figure BDA0005230281160000061 
Figure BDA0005230281160000062
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer materials, and in particular to a polyphenylene sulfide composition and a preparation method and application thereof. Background Art
[0002] Polyphenylene sulfide (PPS) is a special engineering plastic with excellent comprehensive performance. It has intrinsic flame retardant properties, high strength, high rigidity, high insulation and ultra-high heat resistance. It is widely used in the fields of automobile, environmental protection, electronics and electrical, petrochemical, military, etc. In recent years, with the rapid development of the new energy vehicle market, the application of PPS materials in the three-electric system of new energy vehicles has increased significantly.
[0003] However, in the production process of precision manufacturing and complex structural parts, traditional welding technology is often difficult to meet the application requirements of PPS materials due to factors such as accuracy and welding strength. High-precision, high-speed and non-contact laser welding technology provides a new idea for solving this problem. As a crystalline polymer material, the anisotropic crystal structure of PPS will affect the laser transmittance of the material and limit the effect of its laser welding. Therefore, it is urgent to develop a technology to improve the laser transmittance of PPS. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of this application is to provide a polyphenylene sulfide composition and a preparation method and application thereof, aiming to improve the laser transmittance of PPS and improve its laser welding effect.
[0005] In order to achieve the above objectives, in a first aspect, the present application provides a polyphenylene sulfide composition comprising the following components in parts by weight:
[0006] 60-85 parts of PPS resin,
[0007] 15-40 parts of flat glass fiber;
[0008] The PPS resin meets the following requirements: 10A+10B+C≤6050,
[0009] Wherein, Ag / 10min is the melt index of the PPS resin at 316°C and 5kg.
[0010] B℃ is the crystallization temperature of the PPS resin,
[0011] C ppm is the terminal chlorine content of the PPS resin.
[0012] As a crystalline polymer material, the anisotropic crystal structure of PPS will significantly affect the laser transmittance of the material. The crystallization temperature of PPS resin will affect the crystallinity of the composition, thereby affecting the laser transmittance of the composition; the melt index of PPS resin affects the movement of its own molecular chain during processing, thereby affecting the arrangement of the crystal structure with a regular structure, thereby affecting the crystallinity and laser transmittance of the composition; the terminal chlorine content of PPS resin will affect the proportion of reactive groups in the resin, and affect the reactivity of PPS molecules, thereby affecting the interaction between PPS molecules, and further affecting the movement of PPS molecular chains. By controlling the crystallization temperature, melt index and terminal chlorine content of PPS resin to meet the above-mentioned specific relationship, the crystallinity of the composition can be effectively reduced and the laser transmittance can be improved; at the same time, compared with round glass fiber, flat glass fiber has a higher packing density in the composition, which can reduce defects such as unevenness and pores between phase interfaces, which is beneficial to improve the laser transmittance of the composition.
[0013] The polyphenylene sulfide composition has a high laser transmittance and a good laser welding effect under the synergistic effect of specific contents and types of PPS resin and glass fiber, and is suitable for laser welding, such as for related parts of automobiles, electronic and electrical equipment, etc. that have laser welding application requirements.
[0014] In the present application, 10A+10B+C≤6050, such as 6000, 5900, 5800, 5700, 5600, 5500, 5400, 5300, 5200, 5100, 5000 or an interval formed by any two of the above values. In some embodiments, 10A+10B+C is 5000-6010.
[0015] Preferably, A≤200. For example, A is 200, 190, 180, 170, 160, 150 or an interval formed by any two of the above values.
[0016] Controlling A≤200 is beneficial to restricting the movement of the PPS resin molecular chain during processing, reducing the possibility of arranging the PPS resin molecular chain to form a regular crystal structure, and improving the laser transmittance of the composition.
[0017] More preferably, A is 160-190, so as to obtain a low crystallinity product while taking into account the processing performance of the material.
[0018] The A can be obtained by testing at 310° C. and 5 kg load according to ISO1133:2011.
[0019] Preferably, B is less than 220. For example, B is 219, 217, 215, 212, 210, 207, 205, 203, 200, 197, 195, 192, 190 or an interval formed by any two of the above values.
[0020] Controlling B<220 can reduce the crystallinity of the composition and improve its laser transmittance.
[0021] More preferably, the B is 195-215, ensuring that the mechanical properties of the material meet the application requirements of the product.
[0022] The B can be obtained by testing according to GB / T 13464:2008, nitrogen atmosphere, cooling rate 20°C / min.
[0023] Preferably, C is ≤ 2500. For example, C is 2500, 2200, 2000, 1800, 1600, 1400, 1200, 1000, 800, 600 or an interval formed by any two of the above values.
[0024] Controlling the C≤2500 is beneficial to increasing the proportion of reactive groups in the PPS resin, increasing the reactivity of the PPS molecules, increasing the interaction between the components, limiting the movement of the PPS molecular chain, and improving the laser transmittance of the composition.
[0025] More preferably, the C is 1500-2200.
[0026] The C can be obtained by testing using an ion chromatograph in accordance with BS EN14582:2016.
[0027] In some embodiments, the preparation method of the PPS resin comprises the following steps:
[0028] Putting raw materials sodium sulfide nonahydrate, NMP (N-methylpyrrolidone), lithium chloride and sodium hydroxide into a reaction kettle according to the molar ratio of 1: (4-6): (0.5-0.7): (0.04-0.06), stirring continuously at 75-100 r / min under continuous protection of nitrogen, setting the vacuum degree to -0.05--0.09 MPa and heating to 200-220° C. for dehydration to obtain a dehydrated sodium sulfide raw material;
[0029] The dehydrated sodium sulfide and p-dichlorobenzene in an amount of 1 to 1.01 times of the sodium sulfide are added into a reactor for polymerization reaction, and the reaction is carried out at a temperature of 210 to 230° C. for 1 to 3 hours, and at a temperature of 240 to 260° C. for 3 to 5 hours, and after cooling, a PPS resin raw material is obtained;
[0030] Para-hydroxythiophenol is used as an end group regulator and added into a reaction kettle together with the obtained PPS resin raw material, NMP and a sodium hydroxide solution, wherein the molar ratio of the PPS resin raw material, para-hydroxythiophenol, NMP and the sodium hydroxide in the sodium hydroxide solution is 1:(0.05-0.15):(4-6):(1.5-2.5), the mass percentage of sodium hydroxide in the sodium hydroxide solution is 40%-45%, and then the temperature is set at 230-260°C for reaction for 3-5h, and then a high-temperature acid washing treatment is performed to obtain a PPS resin.
[0031] Preferably, the flatness ratio of the flat glass fiber is 2.4-4.2. For example, the flatness ratio of the flat glass fiber is 2.5, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4 or an interval formed by any two of the above values.
[0032] Limiting the flatness ratio of the flat glass fiber to a range of 2.4 to 4.2 is beneficial to reducing defects such as unevenness and pores between phase interfaces and improving the laser transmittance of the composition.
[0033] Preferably, the average short side length of the flat glass fiber cross section is 5-7 μm, and the average long side length is 18-28 μm. For example, the average short side length of the flat glass fiber cross section is 5 μm, 5.2 μm, 5.5 μm, 5.7 μm, 6 μm, 6.2 μm, 6.5 μm, 6.7 μm, 7 μm or an interval formed by any two of the above values; the average long side length is 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm or an interval formed by any two of the above values.
[0034] When the average short side length of the flat glass fiber cross section is 5-7 μm and the average long side length is 18-28 μm, the effect of enhancing the mechanical properties is better.
[0035] The average flatness ratio, average short side length and average long side length of the cross section of the flat glass fiber can be tested and obtained by the following method: a glass fiber sample is observed using a scanning electron microscope, the sizes of 300 glass fibers are measured, and the average value is taken.
[0036] Preferably, the average length of the flat glass fibers is 2-5 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, or an interval formed by any two of the above values.
[0037] The average length of the flat glass fiber can be tested and obtained by the following method: a glass fiber sample is observed using a two-dimensional optical microscope, the sizes of 300 glass fibers are measured, and the average value is taken.
[0038] Preferably, the crystallization temperature of the polyphenylene sulfide composition is less than 210° C. For example, the crystallization temperature of the polyphenylene sulfide composition is 205° C., 203° C., 200° C., 197° C., 195° C., 193° C., 190° C., 187° C., 185° C., 182° C., 180° C., or an interval formed by any two of the above values.
[0039] More preferably, the crystallization temperature of the polyphenylene sulfide composition is 180-200°C.
[0040] The crystallization temperature of the polyphenylene sulfide composition can be measured by the following method: DSC test, nitrogen atmosphere, 30-320° C., test the crystallization temperature in the cooling stage, the cooling rate is 20° C. / min.
[0041] Preferably, the following components are further included in parts by weight: 0 to 1 part of colorant.
[0042] Exemplarily, the colorant includes at least one of aniline black, oil black or carbon black.
[0043] Preferably, the following components are also included in parts by weight: 0.1 to 1 part of processing aid.
[0044] Exemplarily, the processing aid includes but is not limited to at least one of an antioxidant, a lubricant, and the like.
[0045] Exemplarily, the antioxidant includes at least one of antioxidant 1010, RINOX 1098, REVONOX 608, PEP-36, and the like.
[0046] Exemplarily, the lubricant includes at least one of polyethylene wax, zinc stearate, and lithium stearate.
[0047] Without significantly damaging the technology of the present application, the polyphenylene sulfide composition of the present application may further include an anti-ultraviolet agent, the amount of which is 0 to 0.5 parts by weight, such as 0 parts by weight, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight or any two parts by weight. Exemplarily, the anti-ultraviolet agent includes at least one of a cinnamate anti-ultraviolet agent, a hydroxybenzophenone anti-ultraviolet agent, a hydroxyphenylbenzotriazole anti-ultraviolet agent, and the like.
[0048] In some embodiments, the weight percentage of PPS resin in the polyphenylene sulfide composition is above 50%, such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or an interval formed by any two of the above values.
[0049] In a second aspect, the present application provides a method for preparing the polyphenylene sulfide composition, comprising the following steps: mixing all raw materials, melt-extruding, and granulating to obtain the polyphenylene sulfide composition.
[0050] Preferably, the melt extrusion is carried out in a twin-screw extruder, the melt extrusion temperature is 220-300° C., the screw speed is 300-450 rpm, and the screw aspect ratio is (38-42):1.
[0051] In a third aspect, the present application provides application of the polyphenylene sulfide composition in the field of laser welding.
[0052] Compared with the prior art, the beneficial effect of the present application is that the polyphenylene sulfide composition of the present application has a higher laser transmittance under the synergistic effect of specific contents and types of PPS resin and glass fiber, and has a better laser welding effect, and is suitable for laser welding, such as for related parts of automobiles, electronic and electrical equipment, etc. that have laser welding application requirements. DETAILED DESCRIPTION
[0053] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.
[0054] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available raw materials, and the component raw materials used in each parallel experiment are all of the same kind.
[0055] Examples 1 to 7 and Comparative Examples 1 to 4
[0056] These embodiments and comparative examples all provide a polyphenylene sulfide composition, and the preparation method of these polyphenylene sulfide compositions comprises the following steps: 78 parts by weight of PPS resin, 20 parts by weight of glass fiber, 1 part by weight of colorant and 1 part by weight of processing aid are mixed and dispersed, and fed into a twin-screw extruder, and granulated to obtain a polyphenylene sulfide composition;
[0057] The screw length-diameter ratio of the twin-screw extruder is 48:1, the screw speed is 450 r / min, and the melt extrusion temperature is 300°C.
[0058] The information of the PPS resin used in these examples and comparative examples is shown in Table 1. The PPS resin is homemade in-house and the preparation method is as follows:
[0059] (1) The raw materials of hydrated sodium sulfide, NMP, lithium chloride and sodium hydroxide are put into a reactor in a molar ratio of 1:5:0.6:0.05, and stirred continuously at 80r / min under continuous protection of nitrogen. The temperature is raised to 210°C for dehydration under a vacuum degree of -0.05 to -0.09MPa. Depending on the vacuum degree set, sodium sulfide raw materials with different crystal water contents are obtained; the dehydrated sodium sulfide and 1.005 times the amount of p-dichlorobenzene are added to the reactor for polymerization reaction, and the reaction is carried out at a temperature of 220°C for 2h and at 250°C for 4h, and a PPS resin raw material is obtained after cooling. By controlling the degree of dehydration of the raw sodium sulfide, a PPS resin raw material with a melt index in the range of 160-220 at 316°C and 5kg is obtained;
[0060] (2) using p-hydroxythiophenol as an end group regulator, and adding it into a reaction kettle together with the PPS resin raw material, NMP and sodium hydroxide solution obtained in the previous step, wherein the molar ratio of the PPS resin raw material, p-hydroxythiophenol, NMP and the sodium hydroxide in the sodium hydroxide solution is 1:0.1:5:2, and the mass percentage of sodium hydroxide in the sodium hydroxide solution is 45%. Then, the temperature is set at 230-260° C. for 4 hours. Different reaction temperatures can regulate the activity of the PPS end groups, and a crystallization temperature of 195-225° C. is obtained. PPS resin; further by subjecting the PPS resin to high-temperature pickling treatment, its terminal chlorine content can be adjusted to 1500-2500, wherein the meanings of A, B and C are as described above; the glass fiber used is glass fiber 1, model ECS3F-03-568H of Jushi Company, which is a flat glass fiber with an average flatness ratio of 3.8, an average short side length of the cross section of 5 μm, an average long side length of the cross section of 19 μm, and an average length of 3 mm; the colorant used is aniline black; the processing aids used are RINOX 1098, REVONOX 608 and lubricant polyethylene wax, and the mass ratio of the three is 1:2:2.
[0061] Table 1
[0062]
[0063]
[0064] Examples 8 to 13 and Comparative Examples 4 to 5
[0065] These embodiments and comparative examples all provide a polyphenylene sulfide composition. The preparation methods of these polyphenylene sulfide compositions are the same as those of Example 1 except that the glass fibers used are different or the weight ratio of the PPS resin, the glass fibers, the colorant and the processing aid is different from that of Example 1. The specific glass fibers used and the weight ratio of the PPS resin, the glass fibers, the colorant and the processing aid are shown in Table 2. The information of the glass fibers 2 to 7 used is as follows:
[0066] Glass fiber 2: flat glass fiber, average flatness ratio is 2.6, average short side length is 7μm, average long side length is 18μm, average length is 3mm, model TFG-3.0-T436, manufacturer Taishan Fiberglass;
[0067] Glass fiber 3: flat glass fiber, average flatness ratio of 4, average short side length of 7μm, average long side length of 28μm, average length of 3mm, model TFG-3.0-T4355, manufacturer Taishan Fiberglass;
[0068] Glass fiber 4: flat glass fiber, average flatness ratio of 3.8, average short side length of 6μm, average long side length of 23μm, average length of 3mm, model ESC4F-03-584, manufacturer Jushi Glass Fiber;
[0069] Glass fiber 5: flat glass fiber, average flatness ratio of 3, average short side length of 6.8μm, average long side length of 20μm, average length of 3mm, model ECS3F-03-508A, manufacturer Jushi Glass Fiber;
[0070] Glass fiber 6: round glass fiber, average diameter 7 μm, average length 3 mm, model ECS301CL-3-H, manufacturer Chongqing Yuntianhua Group;
[0071] Glass fiber 7: round glass fiber, average diameter 17μm, average length 3mm, model ECS17-3.0-T635H, manufacturer Taishan Fiberglass.
[0072] Table 2
[0073]
[0074]
[0075] The following performance tests were performed on the polyphenylene sulfide compositions of the above examples and comparative examples:
[0076] (1) Crystallization temperature: DSC test, nitrogen atmosphere, 30-320°C, test the crystallization temperature in the cooling stage, cooling rate is 20°C / min;
[0077] (2) Crystallinity: injection molding thickness 2 mm color plate, using XRD test;
[0078] (3) Laser transmittance: The infrared transmittance of the material at a wavelength of 980 nm was tested using an infrared spectrophotometer for a 2 mm thick color plate.
[0079] The test results are shown in Table 3.
[0080] Table 3
[0081] Crystallization temperature / ℃ Crystallinity / % Laser transmittance / % Example 1 185 10 43 Example 2 192 8 45 Example 3 191 16 30 Example 4 195 15 35 Example 5 197 14 35 Example 6 190 12 36 Example 7 188 16 32 Example 8 208 13 31 Example 9 182 9 44 Example 10 189 12 38 Embodiment 11 203 16 34 Example 12 187 14 36 Embodiment 13 201 12 35 Comparative Example 1 233 55 10 Comparative Example 2 228 58 8 Comparative Example 3 221 42 15 Comparative Example 4 210 35 18 Comparative Example 5 207 30 12
[0082] It can be seen from the above data that the polyphenylene sulfide composition obtained in each embodiment of the present application has a crystallization temperature of less than 210° C., a crystallinity of less than 20%, and a laser transmittance of more than 30%.
[0083] From the comparison between Examples 1 to 13 and Comparative Examples 1 to 3, it can be seen that when the PPS resin satisfies 10A+10B+C≤6000, the laser transmittance of the composition is significantly higher.
[0084] From the comparison between Example 1 and Comparative Examples 4 to 5, it can be seen that, compared with round glass fibers, flat glass fibers can significantly improve the laser transmittance of the composition.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solutions of the present application can be modified or replaced by equivalents.
[0086] Without departing from the essence and scope of the technical solution of this application.
Claims
1. A polyphenylene sulfide composition, characterized in that: It comprises the following components in parts by weight: 60-85 parts of PPS resin, 15-40 parts of flat glass fiber; The PPS resin meets the following requirements: 10A+10B+C≤6050, Wherein, Ag / 10min is the melt index of the PPS resin at 316°C and 5kg. B℃ is the crystallization temperature of the PPS resin, C ppm is the terminal chlorine content of the PPS resin.
2. The polyphenylene sulfide composition according to claim 1, characterized in that The 10A+10B+C is 5000~6010.
3. The polyphenylene sulfide composition according to claim 1, characterized in that A≤200, preferably 160-190; and / or The B is less than 220, preferably 195 to 215; and / or The C is ≤2500, preferably 1500-2200.
4. The polyphenylene sulfide composition according to claim 1, characterized in that The average flatness ratio of the flat glass fibers is 2.4 to 4.
2.
5. The polyphenylene sulfide composition according to claim 1, characterized in that The average short side length of the flat glass fiber cross section is 5-7 μm, and the average long side length is 18-28 μm.
6. The polyphenylene sulfide composition according to claim 1, characterized in that The average length of the flat glass fibers is 2-5 mm.
7. The polyphenylene sulfide composition according to claim 1, characterized in that The crystallization temperature of the polyphenylene sulfide composition is less than 210°C, preferably 180-200°C.
8. The polyphenylene sulfide composition according to claim 1, characterized in that The invention also includes the following components in parts by weight: 0.1 to 1 part of a colorant and 0.1 to 1 part of a processing aid; preferably, the colorant includes at least one of aniline black, oil black or carbon black.
9. The method for preparing a polyphenylene sulfide composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing all raw materials, melt-extruding, and granulating to obtain the polyphenylene sulfide composition.
10. Use of the polyphenylene sulfide composition according to any one of claims 1 to 8 in the field of laser welding.
Citation Information
Patent Citations
Nylon 66 composite material as well as preparation method and application thereof
CN117659690A
Polyphenylene sulfide resin compositions
CN1798808A
Polyphenylene sulfide resin composition for laser welding, and composite molded product using it
JP2005015792A